Efektivitas Media Promosi Audio Visual dalam Upaya Pencegahan Hipertensi di Poltekkes Kemenkes Bengkulu - Sarkawi; Ningsih, Lisma (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2024)
Background: The problem of hypertension in Indonesia is still a big challenge with a fairly large prevalence, namely 34.1%. Providing education can change the mindset of hypertension sufferers so that they can change their perception of carrying out self-care and have positive power to recover from their disease. Educational programs can be said to be successful if they are supported by good methods. Therefore, a method is needed to convey information about self-management using audio visual media. Method: This research uses the R&D method with the ADDIE model. The subjects of this research were 2 experts for validation tests and 28 respondents for effectiveness product. The data analysis used is quantitative descriptive analysis and qualitative descriptive data analysis. Results: At the development stage, the material expert's validation assessment obtained a score of 3.49 in the appropriate category, the media expert's assessment obtained a score of 3.72 in the appropriate category. In trial 1, a score of 3.56 was obtained in the appropriate category and in trial 2, a score of 3.61 was obtained in the appropriate category. The effectiveness test shows that audio-visual promotional media is effective in increasing knowledge (p value = 0,000), attitudes (p value = 0,000) and behavior (p value = 0,000) in efforts to prevent hypertension. Conclusion: The results of the research show that audio-visual promotional media gets an appropriate category, and audio-visual promotional media is effective in increasing knowledge, attitudes and behavior in efforts to prevent hypertension in ASN of Poltekkes Kemenkes Bengkulu. Keywords: audio visual, promotion, hipertension, media development